Relationship between knowledge level and compliance with leprosy treatment - Sukardi Jaya, Veronica; Sunarti, Sunarti; Suryani, Dyah (Science Midwifery, 2024)
Indonesia is not immune to the global epidemic of leprosy, an infectious illness. The purpose of this research is to identify any correlation between leprosy treatment adherence and level of knowledge. Data included in this literature review comes from secondary sources rather than primary ones; in other words, it is not based on first-hand observation but rather on the findings of earlier studies. From these five articles, we may infer the following about the respondents: their ages range from zero to fourteen, their levels of education, whether or not they are employed, and the extent to which they know about leprosy: high, medium, and low. The study's findings demonstrate that the five publications provide solid proof that leprosy patients' adherence to treatment is correlated with their level of understanding. The greater the level of information that lepers possess, the more compliant they will be in regards to leprosy treatment.